2013
DOI: 10.1021/ja404520j
|View full text |Cite
|
Sign up to set email alerts
|

Autotransfecting Short Interfering RNA through Facile Covalent Polymer Escorts

Abstract: Short interfering ribonucleic acids (siRNAs) are important agents for RNA interference (RNAi) that have proven useful in gene function studies and therapeutic applications. However, the efficacy of exogenous siRNAs for gene knockdown remains hampered by their susceptibility to cellular nucleases and impermeability to cell membranes. We report here new covalent polymer-escort siRNA constructs that address both of these constraints simultaneously. By simple postsynthetic click conjugation of polymers to the pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
0
34
0
2
Order By: Relevance
“…In the former case, polymers grown from nanoparticles or flat surfaces, dramatically change particles stability, dispersibility and thermomechanical properties, in addition to tremendously enhancing lubricity, antifouling or antibacterial properties (53)(54)(55)(56)(57)(58)(59)(60)(61). Hybrids with proteins or nucleic acids increase stability of proteins in harsh environments, (including temperature, pH, and salts) assist in delivery of genes, and can be used in advanced drug delivery (45,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Figure 1 Results Of Scifinder Search On Various Crp Systemsmentioning
confidence: 99%
“…In the former case, polymers grown from nanoparticles or flat surfaces, dramatically change particles stability, dispersibility and thermomechanical properties, in addition to tremendously enhancing lubricity, antifouling or antibacterial properties (53)(54)(55)(56)(57)(58)(59)(60)(61). Hybrids with proteins or nucleic acids increase stability of proteins in harsh environments, (including temperature, pH, and salts) assist in delivery of genes, and can be used in advanced drug delivery (45,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Figure 1 Results Of Scifinder Search On Various Crp Systemsmentioning
confidence: 99%
“…This was notably observed for a bio-conjugate of P2-stat-P9 and trypsin [74]. pOEGMA has also been used for similar purposes to protect DNA (or RNA) within self-assembled supramolecular structures such as complex coacervate core micelles or by covalent conjugation [75][76][77]. For example, Averick et al [77] modified siRNA with two copies of either P9, P2-stat-P5, or P9-stat-N,N-dimethylaminoethyl methacrylate (DMAEMA), one at each extremity.…”
Section: Shielding Of Biomoleculesmentioning
confidence: 88%
“…pOEGMA has also been used for similar purposes to protect DNA (or RNA) within self-assembled supramolecular structures such as complex coacervate core micelles or by covalent conjugation [75][76][77]. For example, Averick et al [77] modified siRNA with two copies of either P9, P2-stat-P5, or P9-stat-N,N-dimethylaminoethyl methacrylate (DMAEMA), one at each extremity. Interestingly, the authors demonstrated that the polymer-siRNA architecture simultaneously imparted protection from nucleases as well as cell permeability.…”
Section: Shielding Of Biomoleculesmentioning
confidence: 99%
“…However, in current studies of siRNA conjugates, more attention has been paid to the 3′-terminus of sense strand. Meanwhile, there are a few literatures reporting bis-conjugated siRNAs, such as 3′,3″-bis-phospholipidsiRNA conjugate, 12 3′,3″-bis-polymer-siRNA conjugate 13 and 3′,3″-bis-peptide-siRNA conjugate. 14 In our previous research, we used a peptide derivative, CPG, to develop a relatively simple strategy to prepare peptide-siRNA conjugates in which hydrophobic hexapeptide (KALLAL) was conjugated at 3′-terminus of single oligonucleotide.…”
Section: Introductionmentioning
confidence: 99%